An experimental study on oscillatory characteristics of young mangroves behind a portable reef. Issue 1 (2nd January 2023) - Sreeranga, Sindhu; Takagi, Hiroshi; Kubota, Shin-Ichi; Mitsui, Jun
ABSTRACT: Approximately half of the world's mangroves are concentrated in Asia, but they have been logged at an alarming rate. To compensate for this, mangrove plantations are being attempted at various sites but with many failures. In this study, we investigated the role of a small portable reef in protecting young mangrove plants from hydrodynamic disturbances caused by short-period waves. To investigate the effectiveness of such a small reef, an experiment using a large wave flume was conducted with two types of real-sized portable reefs (stone and block reefs). A numerical wave model was also constructed to analyze in detail the turbulence around the reef. Our previous study showed that short-period waves can cause resonant oscillations in young mangrove plants. To confirm whether this occurs even behind a reef system, a young mangrove model made of flexible olefin resin was tested with a small wave flume placed behind porous and non-porous reefs, and its oscillation was precisely measured using a high-speed camera. These experiments yielded several new findings. If appropriately designed, small porous reefs can minimize oscillations with adverse effects and provide a favorable environment for the initial growth of mangroves at restoration sites.